(untitled) (Research, Society and Development, 2020)
This study aims to analyze the consumption of licit and illicit drugs by university students. It is an integrative review, using 12 articles available in the following databases: Scielo, Pubmed and Lilacs. The inclusion criteria were: research that addressed the theme, published in English, Portuguese or Spanish in the form of articles, theses and dissertations in the period from 2012 to 2019. As exclusion criteria: papers that did not present full abstracts in the databases and was not of a scientific nature. In all the analyzed studies, it was verified that the university students mostly use drugs, and that most reported alcohol and tobacco consumption, but also observed the consumption of several illicit drugs such as marijuana, cocaine, among others. It is suggested that there is an incentive to the development of public policies aimed at this public, which diminished the vulnerability of these students. Considering that the consumption of these substances can damage your health and cause other problems during adulthood.